THE ROLE OF TECHNOLOGY IN EFL CLASSROOM - Fahri Haswani (IJEE (Indonesian Journal of English Education), 2014)
In  response  to  an  appeal  from  Indonesia’s  Ministry  of  Education  and  Culture  to  all universities and colleges to improve the quality of tertiary  education toward regional and international standard, language institutions are making great efforts to further promote the  foreign  language  learning  process.  In  the  last  few  years  there  have  been  dramatic changes  in  the  ways  that  languages  are  taught  by communicative  approach  and  the introduction of technological tools. In recent years, the use of technological aids, especially those related to computers, has increasingly become  a common feature of the classroom. There is no doubt that computer based instruction will occupy a more central role in the foreign language classroom in the future. Information technology has drawn the interest of teachers of English as a second or foreign language in non-English speaking countries. The technology integration into  the curriculum is not a single concept which is generated from one  single  theory  nor  does  it  give  full  guidelines  for  the  implementation  in  practical situation. This issue constitutes ideas from many different theories. This paper  discusses the issue of technology contributions in EFL classroom. The question raised in this paper is how technology facilitates  the attainment of course goals.  The answer of the question will help  English  teachers  to  clarify  the  real  problems  of  the  initiative  so  that  the  innovation and possible changes can be aligned with the need of the students. However, this literature review  only  covers  limited  issues  related  with  the  role  of  technology  in  EFL  classroom. Further  discussion  from  other  different  points  of  view  is  still  needed  to  create  more complete description of conceptual foundation of the innovation.